VOCAL ART - A SPECIAL TYPE OF MUSICAL ART (American Journal of Technology and Applied Sciences, 2023)
The article discusses the main essential characteristics of pop vocal art in the context of the specifics of pop-jazz performance. The focus is on musical style, performing traditions, acoustic features of the singer's voice, the physiology of the impact of pop-jazz singing on listeners, the main tasks of the educational process aimed at mastering it.